Influence of friction bearings on the frequency response of a variable stiffness mechanism. (February 2022) - Lindenmann, A.; Heyden, E.; Mas, V.; Krause, D.; Matthiesen, S.
Abstract: This contribution examines a variable stiffness mechanism that is intended for the use as a boundary element in vibration tests. The mechanism consists of two antagonistic nonlinear springs guided along the central axis. The axis is axially guided via two bearings. This paper concerns itself with comparing the effects of friction and roller bearings on the frequency response. Further, a comparison of different measurement techniques for the dynamic characterization of the aforementioned mechanism is in focus. An experimental study utilizing a multisine, sine-sweep, and impulse excitation signal is conducted. A nonlinear numerical model as well as a linear approximation are presented and compared with the measurement results. The results indicate that friction bearings have a strong influence on the frequency response of the system, especially at low displacement amplitudes. The influence of the friction contact on the results of different measurement methods is shown. The presented variable stiffness mechanism with the roller bearing configuration yielded in a predictable vibration behavior even for high mechanism pretensions. Highlights: The design of a variable stiffness mechanism for vibration testing is introduced. An experimental and numerical study was conducted for the dynamic characterization. Analysis of different excitation techniques for the experimental characterization. Comparison of friction bearings and roller bearings and their influence on the frequency response.